TEAMWORK/CLOSENESS TO PATIENT AS ELEMENTS OF PRAXIS OF NURSES IN INTENSIVE CARE - Gustavo de Mello Duarte; Marcelo da Silva Alves (Universidade Federal de Santa Maria, 2014)
http://dx.doi.org/10.5902/217976929059 Aim: to unveil the practice of nurses working in intensive care units. Method: a qualitative study that used the sociology of everyday life and the concept of praxis as Karel Kosic to theoretical foundations. It was conducted through semi-structured interviews with eight nurses from the intensive care unit of a hospital's philanthropic "Zona da Mata " of Minas Gerais (Brazil) in the period of January to April 2012. Data were analyzed by triangulation between categories, reference and experience of the researcher. Results: it was found that with teamwork nurses recognize their own role and other professionals as well as have their work recognized and valued. Therefore, being next to patients helps on creating bonds and meeting patients' needs adequately. Final Thoughts : both factors rescue primordial values nursing assisting in the process of nurses' work and adding to this humanistic values.